Question
upstudy study bank question image url

Solve for \( x \) and \( y \) simultanously (1) \( 3 x+2 y=7 \) and \( -3 x+y=1 \) (2) \( x+3 y=17 \) and \( 4 x-2 y=12 \) (3) \( x+2 y=13 \) and \( 3 x-y=4 \)

Ask by Joseph Carrillo. in South Africa
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: 1. \( x = \frac{5}{9} \), \( y = \frac{8}{3} \) 2. \( x = 5 \), \( y = 4 \) 3. \( x = 3 \), \( y = 5 \)

Solution

Solve the system of equations \( 3x+2y=7;-3x+y=1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+2y=7\\-3x+y=1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}3x+2y=7\\y=1+3x\end{array}\right.\) - step2: Substitute the value of \(y:\) \(3x+2\left(1+3x\right)=7\) - step3: Simplify: \(9x+2=7\) - step4: Move the constant to the right side: \(9x=7-2\) - step5: Subtract the numbers: \(9x=5\) - step6: Divide both sides: \(\frac{9x}{9}=\frac{5}{9}\) - step7: Divide the numbers: \(x=\frac{5}{9}\) - step8: Substitute the value of \(x:\) \(y=1+3\times \frac{5}{9}\) - step9: Calculate: \(y=\frac{8}{3}\) - step10: Calculate: \(\left\{ \begin{array}{l}x=\frac{5}{9}\\y=\frac{8}{3}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=\frac{5}{9}\\y=\frac{8}{3}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(\frac{5}{9},\frac{8}{3}\right)\) Solve the system of equations \( x+3y=17;4x-2y=12 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+3y=17\\4x-2y=12\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=17-3y\\4x-2y=12\end{array}\right.\) - step2: Substitute the value of \(x:\) \(4\left(17-3y\right)-2y=12\) - step3: Simplify: \(68-14y=12\) - step4: Move the constant to the right side: \(-14y=12-68\) - step5: Subtract the numbers: \(-14y=-56\) - step6: Change the signs: \(14y=56\) - step7: Divide both sides: \(\frac{14y}{14}=\frac{56}{14}\) - step8: Divide the numbers: \(y=4\) - step9: Substitute the value of \(y:\) \(x=17-3\times 4\) - step10: Calculate: \(x=5\) - step11: Calculate: \(\left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(5,4\right)\) Solve the system of equations \( x+2y=13;3x-y=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+2y=13\\3x-y=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=13-2y\\3x-y=4\end{array}\right.\) - step2: Substitute the value of \(x:\) \(3\left(13-2y\right)-y=4\) - step3: Simplify: \(39-7y=4\) - step4: Move the constant to the right side: \(-7y=4-39\) - step5: Subtract the numbers: \(-7y=-35\) - step6: Change the signs: \(7y=35\) - step7: Divide both sides: \(\frac{7y}{7}=\frac{35}{7}\) - step8: Divide the numbers: \(y=5\) - step9: Substitute the value of \(y:\) \(x=13-2\times 5\) - step10: Calculate: \(x=3\) - step11: Calculate: \(\left\{ \begin{array}{l}x=3\\y=5\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=5\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(3,5\right)\) The solutions to the given systems of equations are: 1. \( x = \frac{5}{9} \) and \( y = \frac{8}{3} \) 2. \( x = 5 \) and \( y = 4 \) 3. \( x = 3 \) and \( y = 5 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Alright! Let's dive into solving these simultaneous equations! For the first set of equations: (1) \( 3x + 2y = 7 \) (2) \( -3x + y = 1 \) From equation (2), we can express \( y \): \[ y = 1 + 3x \] Now substitute this into equation (1): \[ 3x + 2(1 + 3x) = 7 \] \[ 3x + 2 + 6x = 7 \] \[ 9x + 2 = 7 \] \[ 9x = 5 \] \[ x = \frac{5}{9} \] Now substitute \( x \) back to find \( y \): \[ y = 1 + 3\left(\frac{5}{9}\right) = 1 + \frac{15}{9} = 1 + \frac{5}{3} = \frac{8}{3} \] So the solution is \( x = \frac{5}{9} \) and \( y = \frac{8}{3} \). --- For the second set of equations: (1) \( x + 3y = 17 \) (2) \( 4x - 2y = 12 \) From equation (1), solve for \( x \): \[ x = 17 - 3y \] Substitute this into equation (2): \[ 4(17 - 3y) - 2y = 12 \] \[ 68 - 12y - 2y = 12 \] \[ 68 - 14y = 12 \] \[ -14y = 12 - 68 \] \[ -14y = -56 \] \[ y = 4 \] Now substitute \( y \) back to find \( x \): \[ x = 17 - 3(4) = 17 - 12 = 5 \] So the solution is \( x = 5 \) and \( y = 4 \). --- For the third set of equations: (1) \( x + 2y = 13 \) (2) \( 3x - y = 4 \) From equation (1), solve for \( x \): \[ x = 13 - 2y \] Substituting this into equation (2): \[ 3(13 - 2y) - y = 4 \] \[ 39 - 6y - y = 4 \] \[ 39 - 7y = 4 \] \[ -7y = 4 - 39 \] \[ -7y = -35 \] \[ y = 5 \] Now substitute \( y \) back to find \( x \): \[ x = 13 - 2(5) = 13 - 10 = 3 \] So the solution is \( x = 3 \) and \( y = 5 \). ### Summary of Solutions: 1. \( x = \frac{5}{9}, y = \frac{8}{3} \) 2. \( x = 5, y = 4 \) 3. \( x = 3, y = 5 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy